Proposição e otimização de um medicamento de liberação controlada utilizando planejamento de misturas - Cenerini, Danilo Lauriano (Universidade Federal de São Carlos, 2025)
Innovation and continuous improvements in the development of pharmaceutical forms that can bring, in addition to new solutions, more comfort and life quality for patients, has been a major challenge in the pharmaceutical industries. In this scenario, this study aimed at the development and optimization of a world-changing medicine, an oral pharmaceutical form that acts on the central nervous system. The experimental part used the Quality By Design (QbD) approach with the objective of identifying the main components of the formulation that most affect the obtaining of a controlled-release solid oral medicine in the organism. As it is an innovative medicine worldwide and with few scientific references, the use of QbD becomes a powerful and recommended tool in obtaining the final product. In this sense, the design aimed to identify and challenge the formulation, identifying the main components and parameters that impact the in vitro dissolution profile test, aiming for a formulation with a prolonged release profile over time. In mixtures design, four main excipients of the matrix (retardant agent, disintegrant, thickener and an emulsifier) were varied to obtain four responses that were defined as essential for obtaining an oral solid controlled release anxiolytic, evaluated through: dissolved percentage of active ingredient, floating time, dissolution efficiency and weight variation. The design generated a total of 23 experiments with four authentic replications. The data were obtained from dissolution profiles combined with the high performance liquid chromatography (HPLC) technique.
Proposition and optmization of a controlled release pharmaceutical product using misture design
Keywords: Quimiometria; Chemometrics; Liberação controlada; Controlled release; Mixture design; Sistema nervoso central; Central nervous system; OUTROS::QUIMICA INDUSTRIAL